Effect of anatomo-topographic and sonographic Polarity of the thyroid nodules on the thyroid malignancy by evaluating its impression on the relationship between the Bethesda System, TBSRTC, Strain Elastography Score and the thyroid histopathology - Demet, Sengul; Ilker, Sengul (Sanamed, 2019)
Background: The goal is to evaluate the association between the topo-sonographic polarity of the thyroid nodules and the thyroid malignancy by analyzing its effect on The Bethesda System for Reporting Thyroid Cytopathology (TBSRTC), score of Strain Elastography (SE) for thyroid as Tsukuba Elasticity Score (TES), and histopathologic assessment. Material and Methods: A preliminary single-center retrospective study was carried out by including the documents of 641 consecutive eligible patients, possessing 770 thyroid nodules which undergone neck ultrasonography (US), Doppler US, SE, and US-guided-fine needle aspiration (FNA) during April 2011 to April 2017. The stiffness had been measured by TES of SE. The ability of the prediction of the malignancy by the polarity of 770 thyroid nodules considering the association between; i) TBSRTC and histopathology and ii) TES and histopathology had been evaluated. Results: Of the 770 thyroid nodules evaluated, 408 (53.0%) were located at the superior pole (Pol 1) while 362 (47.0%) were at the inferior pole (Pol 0) with 0.9046 AUC and 0.8171 AUC for the association between TBSRTC and histopathology and 0.9280 AUC and 0.7888 AUC for the association between TES and histopathology, respectively. However, those difference were not significant for Pol 1, topographically. Conclusion: The topograghic and sonographic polarity of the thyroid nodules may not be useful for estimating the thyroid malignancy by using the association between TBSRTC and histopathology with TES and histopathology. However, the association with Pol 1, the superior thyroid pole, was stronger though the difference was not significant.